Observations of meteoritic material and implications for aerosol nucleation in the winter Arctic lower stratosphere derived from in situ particle measurements - Curtius, J.; Weigel, R.; Schlager, H.; Dreiling, V.; Borrmann, S.; Vössing, H.-J.; Wernli, H.; Werner, A.; Volk, C.-M.; Konopka, Paul; Krebsbach, M.; Schiller, C.; et al. (EGU, 2005)
Number concentrations of total and non-volatile aerosol particles with size diameters > 0.01 mu m as well as particle size distributions (0.4 - 23 mu m diameter) were measured in situ in the Arctic lower stratosphere ( 10 - 20.5 km altitude). The measurements were obtained during the campaigns European Polar Stratospheric Cloud and Lee Wave Experiment (EUPLEX) and Envisat-Arctic-Validation (EAV). The campaigns were based in Kiruna, Sweden, and took place from January to March 2003. Measurements were conducted onboard the Russian high-altitude research aircraft Geophysica using the low-pressure Condensation Nucleus Counter COPAS (COndensation PArticle Counter System) and a modified FSSP 300 ( Forward Scattering Spectrometer Probe). Around 18 - 20 km altitude typical total particle number concentrations n(t) range at 10 - 20 cm(-3) ( ambient conditions). Correlations with the trace gases nitrous oxide (N2O) and trichlorofluoromethane (CFC-11) are discussed. Inside the polar vortex the total number of particles > 0.01 mu m increases with potential temperature while N2O is decreasing which indicates a source of particles in the above polar stratosphere or mesosphere. A separate channel of the COPAS instrument measures the fraction of aerosol particles non-volatile at 250 degrees C. Inside the polar vortex a much higher fraction of particles contained non-volatile residues than outside the vortex ( similar to 67% inside vortex, similar to 24% outside vortex). This is most likely due to a strongly increased fraction of meteoric material in the particles which is transported downward from the mesosphere inside the polar vortex. The high fraction of non-volatile residual particles gives therefore experimental evidence for downward transport of mesospheric air inside the polar vortex. It is also shown that the fraction of non-volatile residual particles serves directly as a suitable experimental vortex tracer. Nanometer-sized meteoric smoke particles may also serve as nuclei for the condensation of gaseous sulfuric ...